PENGGUNAAN PROTEIN PADA AYAM BROILER YANG DIBERI RANSUM ECENG GONDOK (Eichornia crassipes) FERMENTASI - P. Wardaya; L. D. Mahfudz; N. Suthama (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The research was aimed to analyze the effect of feeding fermented water hyacinth on protein utilization in broiler chicken. The experimental animals were 144 broiler chickens of 14 days old with an average body weight 355,91 ± 16,95 g. The experiment was assigned in a completely randomized design with 4 treatments and 6 replications (6 birds each). The treatment applied were fermentated water hyacinth in the ration as follows : 0% (T0), 5% (T1), 10% (T2); 15% (T3). The parameter observed were protein consumption, protein digestibility, body weight again and protein efficiency. The results showed that feeding fermented water hyacinth significantly decreased protein consumption, protein digestibility and body weight again, but not for protein efficiency on the level of trust 5%. The conclusion of the research is that feeding fermented water hyacinth in broiler chicken can be applied at the level of 10% because it produces protein efficiency similar with the ration without water hyacinth.